2018
DOI: 10.1017/jns.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

A pilot feasibility study exploring the effects of a moderate time-restricted feeding intervention on energy intake, adiposity and metabolic physiology in free-living human subjects

Abstract: This pilot study explored the feasibility of a moderate time-restricted feeding (TRF) intervention and its effects on adiposity and metabolism. For 10 weeks, a free-living TRF group delayed breakfast and advanced dinner by 1·5 h each. Changes in dietary intake, adiposity and fasting biochemistry (glucose, insulin, lipids) were compared with controls who maintained habitual feeding patterns. Thirteen participants (29 (sem 2) kg/m2) completed the study. The average daily feeding interval was successfully reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
206
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(234 citation statements)
references
References 20 publications
18
206
0
10
Order By: Relevance
“…Human TRE studies providing all food to maintain isoenergetic intake have reported weight stability with variable effects on glycemic measures (4‐6). Human studies on TRE with ad libitum intake have reported modest weight loss (approximately 3%, 3 kg) (3,7‐9), although glycemic measures remained unchanged (7‐9).…”
Section: Introductionmentioning
confidence: 99%
“…Human TRE studies providing all food to maintain isoenergetic intake have reported weight stability with variable effects on glycemic measures (4‐6). Human studies on TRE with ad libitum intake have reported modest weight loss (approximately 3%, 3 kg) (3,7‐9), although glycemic measures remained unchanged (7‐9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, dietary strategies that focus on the timing of eating and duration of fasting (i.e., chrono-nutrition), rather than the type, quality or quantity of foods, have been demonstrated to improve metabolic health independent of weight loss [12,13]. Specifically, time-restricted feeding (TRF, in which daily food intake is restricted to between 8-10 h) is a dietary strategy that has emerged as a practical intervention for weight loss, and improving insulin resistance along with other markers of whole-body health [10,[12][13][14][15][16]. Controlled (i.e., meals provided) 'early' TRF (eTRF; 0800-1500 h) improved both beta cell function in men with prediabetes [13] and 24-h glucose area under the curve (AUC) in individuals with obesity [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot study by Antoni et al, 2018, 16 hours fasting for the duration of 10 weeks, was able to produce a significant reduction in % body fat with no change in body weight in 13 overweight participants. This suggests a compensatory increase in lean tissue mass during the intervention 43 .…”
Section: Time-restricted Feedingmentioning
confidence: 87%
“…Although TRF was or wasn't able to achieve weight loss, the studies have reported a reduction in adiposity 43 and improvement in insulin sensitivity 40 with the increased fasting window (16-18 hours of fasting). In a pilot study by Antoni et al, 2018, 16 hours fasting for the duration of 10 weeks, was able to produce a significant reduction in % body fat with no change in body weight in 13 overweight participants.…”
Section: Time-restricted Feedingmentioning
confidence: 99%